Формування пізнавальної активності учнів початкової школи - Ходарченко, Світлана (My University, 2025)
Кваліфікаційна робота містить два розділи. У першому розділі представлено результати теоретичного вивчення суті пізнавальної активності учнів. Теоретично вивчено основні підходи до формування пізнавальної активності учнів у передовому педагогічному досвіді. Вивчено умови формування пізнавальної активності, її рівні сформованості. Досліджено психологічні особливості формування пізнавальної активності. На підставі виявлених закономірностей формування пізнавальної активності теоретично обґрунтовано педагогічні умови формування пізнавальної активності в учнів початкової школи. У другому розділі описано зміст проведеного педагогічного експерименту. Описано результати констатувального, формувального та контрольного етапів педагогічного експерименту. Описано шляхи впровадження в освітній процес розроблених педагогічних умов формування пізнавальної активності учнів початкової школи. У процесі проведеного педагогічного експерименту було доведено ефективність розроблених педагогічних умов формування пізнавальної активності учнів початкової школи. The qualification work contains two sections. The first section presents the results of a theoretical study of the essence of students' cognitive activity. The main approaches to the formation of students' cognitive activity in advanced pedagogical experience have been theoretically studied. The conditions for the formation of cognitive activity and its levels of formation have been studied. The psychological features of the formation of cognitive activity have been investigated. Based on the identified patterns of cognitive activity formation, pedagogical conditions for the formation of cognitive activity in primary school students are theoretically substantiated. The second section describes the content of the conducted pedagogical experiment. The results of the ascertaining, formative and control stages of the pedagogical experiment are described. The ways of implementing the developed pedagogical conditions for the formation of cognitive activity of primary school students into the educational process are described. In the course of the conducted pedagogical experiment, the effectiveness of the developed pedagogical conditions for the formation of cognitive activity of primary school students was proven.
Keywords: пізнавальна активність; формування пізнавальної активності; педагогічні умови; учні початкової школи; cognitive activity; formation of cognitive activity; pedagogical conditions; primary school students